Synergistic Anti-Diabetic Potential of Moringa oleifera Leaf Extract and Metformin in Streptozotocin-Induced Diabetic Rats: Biochemical, Histopathological, and Molecular Insights - Haripriya Yadav; Dr. Ramdarshan; Dr. Ajay Singh Thakur; Dr. Yogesh Sharma; Dr. Deepak Koshti (The Bioscan, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion, insulin resistance, or both. Despite the availability of several pharmacological agents, current therapies often fail to fully address oxidative stress, inflammation, and progressive β-cell dysfunction, which are central to diabetic complications. Moringa oleifera, a medicinal plant rich in flavonoids, phenolic acids, and isothiocyanates, exhibits strong anti-hyperglycemic, antioxidant, and anti-inflammatory effects. Metformin, a first-line oral anti-diabetic drug, effectively reduces hepatic glucose production and enhances insulin sensitivity but is limited by gastrointestinal side effects and modest antioxidant activity. This study investigates the synergistic potential of ethanolic Moringa oleifera leaf extract and metformin in streptozotocin (STZ)-induced diabetic Wistar rats. The combination therapy was evaluated through glycemic parameters [fasting blood glucose (FBG), oral glucose tolerance test (OGTT), and glycosylated hemoglobin (HbA1c)], serum insulin, oxidative stress biomarkers [malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione (GSH)], pro-inflammatory cytokines (IL-1β, TNF-α, IL-6), histopathological assessments, and gene expression analysis of GLUT4, IRS1, PI3K, and Akt. The results demonstrated that the combination significantly reduced hyperglycemia, improved glucose tolerance, restored β-cell morphology, enhanced antioxidant defenses, and suppressed pro-inflammatory cytokines more effectively than individual treatments. Moreover, renal and retinal markers indicated protective effects against diabetic nephropathy and retinopathy. These findings suggest that Moringa oleifera and metformin act through complementary mechanisms, achieving superior efficacy in glycemic control and complication prevention while maintaining a favorable safety profile. The study highlights the potential of integrating herbal extracts with conventional drugs for cost-effective and sustainable diabetes management, particularly in resource-limited settings.